2017
DOI: 10.5194/bg-14-4851-2017
|View full text |Cite
|
Sign up to set email alerts
|

Ecophysiological modeling of photosynthesis and carbon allocation to the tree stem in the boreal forest

Abstract: Abstract. A better understanding of the coupling between photosynthesis and carbon allocation in the boreal forest, together with its associated environmental factors and mechanistic rules, is crucial to accurately predict boreal forest carbon stocks and fluxes, which are significant components of the global carbon budget. Here, we adapted the MAIDEN ecophysiological forest model to consider important processes for boreal tree species, such as nonlinear acclimation of photosynthesis to temperature changes, can… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 49 publications
1
26
0
Order By: Relevance
“…In contrast, because precipitation is more abundant in summer (June to September) in northeastern Canada (Naulier et al, 2014), high summer temperatures should be always beneficial to tree growth if enough soil water is available. Therefore, in agreement with GPP-derived eddy covariance data from the Fluxnet network (see Gennaretti et al, 2017a), a better fit between observations and simulations is observed when using a unimodal rather than a bimodal GPP distribution. Monitoring of tree physiology, environmental conditions and wood cell formation will provide a more detailed representation of the complex biological and ecological processes operating in Patagonia, allowing us to run the MAIDENiso model with better constraints.…”
Section: Relative Performance In Modelling δ 18 O Tr Valuessupporting
confidence: 78%
See 3 more Smart Citations
“…In contrast, because precipitation is more abundant in summer (June to September) in northeastern Canada (Naulier et al, 2014), high summer temperatures should be always beneficial to tree growth if enough soil water is available. Therefore, in agreement with GPP-derived eddy covariance data from the Fluxnet network (see Gennaretti et al, 2017a), a better fit between observations and simulations is observed when using a unimodal rather than a bimodal GPP distribution. Monitoring of tree physiology, environmental conditions and wood cell formation will provide a more detailed representation of the complex biological and ecological processes operating in Patagonia, allowing us to run the MAIDENiso model with better constraints.…”
Section: Relative Performance In Modelling δ 18 O Tr Valuessupporting
confidence: 78%
“…It explicitly allocates carbohydrates to different carbon pools (leaves, stem, storage and roots) on a daily basis using phenological stage-dependent rules (see Gennaretti et al, 2017a, for details on the construction of the main MAIDEN model).…”
Section: Modelling Oxygen Isotopes In Tree Ring Cellulose With Maidenisomentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, there are many ecophysiological modeling researches published at multiple spatio-temporal resolutions and spans, including point scales [8,9], mesoscales [10,11] and global scales [12] at yearly [13] or minute time-steps [1], while few of them completely considered the soil water processes and the non-linear relationship between it and vegetation ecophysiological processes. Due to the limited understanding of water-carbon interactions, many researches (regardless of modeling or measurement) often regard them as an isolated process [2].…”
Section: Introductionmentioning
confidence: 99%